Effect Of Compensation, Job Satisfaction, and Organizational Commitment on Employee Performance : Pengaruh Kompensasi, Kepuasaan Kerja, dan Komitmen Organisasi terhadap Kinerja Karyawan - Khurniansyah, Sirotjudin Arsyad; Andriani, Dewi (Indonesian Journal of Law and Economics Review, 2023)
Thissstudyyaimsstoodetermineetheeimpact offcompensation, jobbsatisfactionnanddorganizational commitmenttonnemployeeeperformanceeat theehospital. Thissresearch uses quantitative research using hypothesis testing. The sample used in this study were 85 nurses in the Surabaya area. The analytical tool used in this study uses statistical software. Thissstudyyaimsstoodetermineetheeimpact offcompensation, jobbsatisfactionnand organizational commitmenttonnemployeeeperformanceeat theehospital. The primary data in this study was originally based on a questionnaire. The results of the study explain that (1) compensation has an effect onnemployeeeperformance, (2) job satisfaction has an effect on employee performance, (3) organizational commitment has an effect on employee performance.